Morfologi Akar Tanaman Jagung (Zea mays L.), Serapan Hara N, P, dan K Akibat Pemberian Beberapa Jenis Biochar pada Tanah Bekas Galian Tambang - Darusman Darusman; Syakur Syakur*; Zaitun Zaitun; Yadi Jufri; Manfarizah Manfarizah (Universitas Syiah Kuala, 2021)
Bamboo chips, palm shells, and rice husks waste are environmental pollutants, but have the potential to be processed by pyrolysis to become biochar. Biochar is organic products rich in carbon, high in micro pores and very suitable for amending degraded (damaged) lands. Quality of biohar to be used as a soil amendment is highly dependent on is the raw material (feedstocks) to make biochar itself. The research objective was to find out the most suitable type of biochar to be used as a soil amendment for ex-mining land, so that the growth and production of plants can be optimum. The research has been carried out in the experimental station of the Syiah Kuala University Banda Aceh from August to December 2019 using soil from ex-excavated coal mines of PT. Mifa in West Aceh, Aceh Province. The plant parameters studied were morphological parameters of plant roots (length, weight, specific root length and ratio of roots to plant shoot), nutrient uptake of N, P, and K planted on ex-mine excavated soil. The study was designed using a non-factorial randomized block design consisting of two observation treatment factors, namely the type of biochar treatment (bamboo, palm shell, rice husk) and the dose of biochar (0, 10, 20 ton ha-1), and repeated 3 times. The observations that were observed included the components of root morphology and nutrient uptake of N, P and K plants. Biochar characteristics were analyzed using a Scanning Electron Microscope (SEM). Chemical-physical analyses of soil and plants were based on the procedure issued by the Soil Research Institute, Bogor. The effect among treatments was carried out by a variance analyses test (ANOVA) and if there was an effect, the honestly difference test (Tuckey-HSD) was continued at the level of 0.05. The results showed that the type of biochar had a significant effect on root morphology and nutrient uptake of N, P and K plants. Application biochar of rice husk with the amount of 20 tons ha-1 showed the best treatment for all the parameters studied, this is because nitrogen content in rice husk biochar contribute to growing corn crop. This study also found that bamboo biochar and palm shells gave a negative response when the amount of administration was increased to 20 tonnes ha-1 except for rice husk biochar.